E-Service Quality as a Formative Higher-Order Construct: Mediating Role of Usefulness in Intention to Use E-Cards in Nepalese Digital Era - Bhim Kumar Thapa; Ramesh Rasik Paudel; Rajesh Kumar Chaulagain (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
The paper explores how E-Service Quality (E-SQ) influences the Intention to Use E-cards (ITU) in Nepal with the mediating variable of Usefulness (UFN). The aim of the research is to offer empirical facts based on the dimensions of service quality and its effect on digital financial adoption in an emerging economy setting. The explanatory research design of positivist philosophy and deductive rationale approach was used. A structured questionnaire was used to collect data via Google Forms to 389 E-cards users and the sample size was calculated using Cochran formula. The purposive sampling and a cross-sectional quantitative approach were applied for the selection of relevant participants. The dataset had acceptable common method bias that was below the 50 percent mark. Measurement and structural model were analyzed using SmartPLS. Outer loadings, Cronbach alpha, composite reliability, AVE, HTMT ratio, Fornell-Larcker ratio and VIF values were used to confirm reliability and validity. The findings show that E-service quality has a positive impact on intentions to use as well as perceived usefulness of E-cards. Usefulness similarly plays a major direct role in adoption intention and partially mediates the correlation between quality of service and intention. The results are related to the Technology Acceptance Model (TAM), which proves the significance of perceived usefulness as an instrument by which service quality influences behavioral intention. This study has indicated that efficiency, reliability, responsiveness, security and satisfaction of E-card services would directly boost adoption and at the same time raise perceived usefulness. Technical enhancements should be highlighted as well as the communication of utility benefits to enhance digital financial inclusion by policy makers and service providers. The study is the extension of TAM that introduces conceptualization of E-service quality as a formative higher-order variable and empirically tests the presence of its impact on the digital financial adoption in the Nepalese setting.